Hubungan Indeks Massa Tubuh dengan Kadar Asam Urat Darah pada Penduduk Desa Banjaranyar Kecamatan Sokaraja Kabupaten Banyumas - Kumalasari, Tyas Sitaresmi; Saryono,; Purnawan, Iwan (Jurusan Keperawatan FIKES UNSOED, 2009)
Uric acid is a weak acid that distributed throughout the extracellular fluid as a sodium urate . The amount of uric acid on the blood is influenced by dietary intake of purines, uric acid biosynthesis of the body and rate of uric acid excretion. Indonesian had nutrient problems on the globalization, where human lifestyle and meal pattern have canged. The result of body mass index of survey on the 1995-1997 at the 27 of province show that prevalence of obessity is 6,8% on man and 13,5% on woman.The aim this study was to know the correlation between body mass index with blood uric acid levels of the society Banjaranyar Sokaraja of Banyumas. The cross sectional study used to assess body mass index, and blood uric acid in 52 respondent that fulfill in inclution criteria. Sample research taken by simple random sampling.The average of body mass index and blood uric acid were normal cathegory, it was 27 respondent (51,92%), and normal blood uric acid levels cathegory was 41 respondent (78,85%). The correlation between body mass index with blood uric acid levels on man was r=-0,09 with p=0,70>?=0,05 and on woman was r=0,05 with p=0,80>?=0,05. There was no correlation between body mass index with blood uric acid levels of the society Banjaranyar Sokaraja Banyumas.